Study of maternal and infant factors affecting under nutrition in less than six months - Menon, Pramila; Muthukumar, Aarthi; Mane, Shailaja; Deshmukh, Madhura; Giri, Purushottam (Indian Journal of Community Health, 2024)
Background: Under nutrition in infants is a critical public health concern with irreversible consequences on child growth and development, particularly during the crucial first six months of life. Maternal under nutrition has been associated with poor fetal growth which may result in low birth weight. Aims & Objectives: To understand the clinical profile and management of under nutrition in less than six months. This study aims to explore into the various factors of under nutrition in infants less than 6 months of age, identifying key factors that contribute to the problem and proposing practical solutions to address it. Methodology: This observational cross-sectional study was carried out in a tertiary care hospital with sample size of 194 infants.The pre validated questionnaire and structured proforma was used. Results: The infants aged between 0 and 6 months (average age 2.7± 1.5 months), a total of 194 infants,70.1% required NICU admissions,15.5% had congenital anomalies, 69.6% had weight for age, 39.2% length for age and 46.9% HC for age below -3 standard deviations and Weight for length <-3SD was observed in 57% of infants. Conclusion: Maternal parity, consanguineous marriages, and lower socioeconomic status shown to be associated with the congenital anomalies and low birth weight.